An optimization technique for cropping patterns and land consolidation: A case study for irrigation network - Azim Shirdeli; Somayeh Dastvar (Management Science Letters)
During the past few decades, there has been growing interest in water resources management. Presently, there are many areas in middle east facing with shortage of water for agricultural activities. Therefore, there is a growing concern to have efficient usage of water through optimization techniques. This paper presents a study to maximize famers’ revenue by developing a mathematical model subject to some land and water constraints. The proposed study has been applied for a case study of agricultural program in city of Abhar, Iran and the preliminary results indicate that it could increase the efficiency of agricultural program, significantly. In our survey, the optimal cultivation yields for four five-year programs have increased the income by 20.81, 44.698, 87.18 and 250.34 percent, respectively. In addition, 7.27% development land is added to agricultural lands, there is a 17% increase in water utilization and the productivity is increased from 50% to well above 77% after four 5-year programs have been implemented.